The Disability Studies in Education Annual Conference: Explorations of Working Within, and Against, Special Education - Connor, David (Disability Studies Quarterly, 2014)
This article focuses on the Disability Studies in Education (DSE) conference as an example of expanding disability studies (DS). First, the origins, purpose, and history of the DSE conference are described as a valid alternative discipline to special education. Second, the following three questions are posed in relation to DSE scholars: (1) To what degree can we transgress within existing structures of teacher education and doctoral programs without being provided lip-service, coopted, or dismissed as ideological versus practical? (2) To what degree can we engage (and critique) the field of special education within its journals and conferences—and provide a greater plurality of perspectives within them? And, (3) how can we strategize to widely circulate ideas within DSE throughout education and its related fields? Presentations from the 2012 DSE conference are analyzed, described, and used as a collective response to help answer these questions. Fourth, DSE scholars share post-conference thoughts on the future of DSE. Finally, the deep debt of DSE to DS is acknowledged, along with speculation about possible ways in which DSE may help inform the growth of DS. Keywords: disability studies in education, critical special educators, teacher education, research in education, ideology